2019
DOI: 10.1016/j.molp.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Tiller Bud Formation Regulators MOC1 and MOC3 Cooperatively Promote Tiller Bud Outgrowth by Activating FON1 Expression in Rice

Abstract: Tillering in rice is one of the most important agronomic traits. Rice tiller development can be divided into two main processes: the formation of the axillary bud and its subsequent outgrowth. Several genes critical for bud formation in rice have been identified by genetic studies; however, their molecular functions and relationships are still largely unknown. Here, we report that MONOCULM 1 (MOC1) and MONOCULM 3/ TILLERS ABSENT 1/STERILE AND REDUCED TILLERING 1 (MOC3/TAB1/SRT1), two vital regulators for tille… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 48 publications
1
57
0
1
Order By: Relevance
“…There are at least 13 WOX proteins in rice (Oryza sativa L.) The MONOCULM 3/TILLERS ABSENT 1/STERILE AND REDUCED TILLERING 1 (MOC3/TAB1/SRT1) protein, an ortholog of WUSCHEL, is required for tiller bud formation and female fertility in rice, and has a complex relationship with cytokinins [15,16]. The MOC1 and MOC3 proteins physically interact to regulate tiller bud outgrowth by upregulating the expression of FLORAL ORGAN NUMBER1 (FON1), the orthologs of CLAVATA1 in rice, in a similar manner to CLV signaling in Arabidopsis [17]. The rice narrow leaf2 and narrow leaf3 loci encode an identical OsWOX3A (OsNS) transcriptional activator, orthologs to NARROW SHEATH1 (NS1) and NS2 in maize (Zea mays L.) and PRESSED FLOWER in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…There are at least 13 WOX proteins in rice (Oryza sativa L.) The MONOCULM 3/TILLERS ABSENT 1/STERILE AND REDUCED TILLERING 1 (MOC3/TAB1/SRT1) protein, an ortholog of WUSCHEL, is required for tiller bud formation and female fertility in rice, and has a complex relationship with cytokinins [15,16]. The MOC1 and MOC3 proteins physically interact to regulate tiller bud outgrowth by upregulating the expression of FLORAL ORGAN NUMBER1 (FON1), the orthologs of CLAVATA1 in rice, in a similar manner to CLV signaling in Arabidopsis [17]. The rice narrow leaf2 and narrow leaf3 loci encode an identical OsWOX3A (OsNS) transcriptional activator, orthologs to NARROW SHEATH1 (NS1) and NS2 in maize (Zea mays L.) and PRESSED FLOWER in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…Between Tillering and Pre-tillering, 1140 target genes of miRNA were identified and categorized into 42 GO functional subcategories which were fewer than between Ch-3 and Ch-5. Molecular function (MF) showed the highest enrichment in Tillering and Pre-tillering, and oxidoreductase activity (32, 9.58%), coenzyme binding (19, 5.69%) and cofactor binding (21,6.29%) were the most abundant GO terms, which were different with the dominant GO terms enriched in BP and CC in Ch-3 and Ch-5. However, we found some coenriched target genes in both Ch-3/Ch-5 and Tillering/ Pre-tillering groups using KEGG analysis ( Fig.…”
Section: Prediction and Enrichment Of Mirna Target Genesmentioning
confidence: 98%
“…Under optimal growth environment, tall fescue develops tertiary, quartus and more tillers. It is well reported that tillering is a complex trait that can be regulated by multiple factors such as endogenous hormones level, water, fertilizer, light, temperature, genes, and miRNA [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The development of genome-editing technology has revolutionized agricultural studies, enabling the improvement of different plant traits [1][2][3][4][5]. Various tools have been widely used for precise genome editing in plants, including clustered regularly interspaced short palindromic repeats (CRISPR) based gene editing techniques, such as CRISPR/CRISPR associated protein 9 (Cas9), CRISPR/Cas12a (Cpf1), and CRISPR/Cas13 [6][7][8][9], owing to their reliability.…”
Section: Introductionmentioning
confidence: 99%